Diversidade genética de acessos de Nephelium lappaceum L. através de caracterização morfológica e molecular - De Andrade, Renata Aparecida [UNESP]; Wickert, Ester [UNESP]; Martins, Antonio Baldo Geraldo [UNESP]; De Andrade, Mariana Macedo Costa [UNESP]; De Macedo Lemos, Eliana Gertrudes [UNESP] (My University, 2011)
The rambutan (Nephelium lappaceum) is an exotic fruit with great market potential in Brazil. However, there are few available informations about plants with potential for cultivation, because great morphologic variation is observed among plants and for consequence, little uniformity in the orchards and in the fruits. This research had for objective to evaluate the genetic diversity of a collection of rambutan plants obtained by seeds through morfo-chemical analyses of plants and fruits and by fAFLP molecular markers, to indication of promising materials to be used in new plantings of the culture in the São Paulo State. Was verified that both markers, morphologic and molecular, were efficient in the distinction of varieties, showing the presence of genetic variability among the plants of this study. Was also verified that the materials A51 and B03 presented a larger group of desirable characteristics for new cultivations of the fruitful.
Nephelium lappaceum L. genetic diversity by morphological and molecular characterization
Keywords: FAFLP; Genetic variability; Rambutan; Nephelium lappaceum